The gender authorship gap in gynecologic oncology research - Courtney A. Penn; Jasmine A. Ebott; Daniel B. Larach; Ashley M. Hesson; Jennifer F. Waljee; Marilyn Green Larach (Elsevier, 2019)
Female first authorship and senior authorship in academic obstetrics and gynecology has increased over time but gender-specific publishing data are lacking within gynecologic oncology. We examined contribution by gender to the subspecialty's flagship journal, Gynecologic Oncology, over five decades, from 1972 to 2014, to identify trends in gender representation. Chi-square tests were used to compare gender distributions within and between the first and last years studied (1972-73 and 2014) as well as linear regression to model trends over time. Female first and senior authorship increased significantly from 1972 to 2014 (first: χ2 = 20.9, p < .01; senior: χ2 = 9.9, p < .01). The number of female first authors increased markedly after 2000. Male senior authors still outnumber female senior authors. Papers with senior female authors were more likely to have female first authors, suggesting a mentorship role. Subspecialty-wide gender equity initiatives should encourage continued mentorship of women by female colleagues. Keywords: Gender, Female, Authorship, Gynecologic oncology